Socioeconomic Status Moderates the Effect of Inflammation on Whiter Matter Hyperintensity Burden and Neurodegeneration in Hispanic Older Adults: A Healthy Aging Brain Study‐Health Disparities. (20th December 2022) - Clark, Alexandra L; Haley, Andreana; Evangelista, Nicole D.; Ortega, Nazareth; Dekhtyar, Maria; Foret, Janelle T
Abstract: Background: Hispanic/Latino (H/L) older adults are at increased risk for AD, demonstrate an earlier age of dementia onset, and are more likely to experience delays in AD diagnosis and treatment relative to Non‐Hispanic Whites. These racial/ethnic disparities are the consequence of structural inequities and socioeconomic disadvantages (e.g., income, education) that disproportionately affect H/Ls and promote pathologic inflammatory cascades. Although low socioeconomic status (SES) and inflammation have independently been linked to poor cognitive outcomes, their effects on neural markers of brain health in older adults have yet to be fully examined. Therefore, the present study examined the independent and interactive effects of inflammation and SES on brain markers of neurodegeneration in Hispanic older adults. Method: Data from 524 H/L (428 = cognitively normal; 105 = mild cognitive impairment) older adults enrolled in the Health Aging Brain Study‐Health Disparities were included. Z‐scores for income and years of education were averaged to estimate SES. A principal component analysis was used to create a composite measure of inflammation from serum markers (IL‐6, TNFα). MRI brain scans characterized intracranial volume, white matter hyperintensity (WMH) burden, and neurodegeneration of an AD‐signature meta‐ROI. Multiple linear regressions were used to examine (1) the independent effects of inflammation and SES and (2) inflammation x SES interactions on brain MRI markers. Result: Regression analyses controlling for age, intracranial volume, sex, and vascular risk revealed that inflammation and SES were not significantly associated with WMH burden (ps >.15) or neurodegeneration (ps >.35). However, results revealed significant SES x inflammation interactions on WMH (p = .02) and neurodegeneration (p = .004); examination of simple main effects revealed that inflammation was associated with higher WMH burden and neurodegeneration in individuals from a lower SES, but not in those from a higher SES. Conclusion: Inflammation negatively impacts brain health in H/Ls from a low SES. Results suggest that inflammation is a potentially modifiable point of prevention and intervention underlying poor brain health in H/L older adults from a lower SES. Importantly, results provide a foundation for further characterization of the contributions of systemic racism and barriers to brain health equity in minoritized and marginalized community members.